Overdrive Ventricular Pacing in Pacemaker Recipients with Permanent Atrial Fibrillation and Sleep Apnea - Bordier, Philippe (American Academy of Sleep Medicine, 2012)
STUDY OBJECTIVES: Cardiac pacing is ineffective in obstructive sleep apnea (SA), but it can alleviate central SA/Cheyne-Stokes respiration (CSA) in patients with heart failure (HF). We examined whether overnight overdrive ventricular pacing (OVP) has an effect on SA in pacemaker recipients with permanent atrial fibrillation (AF). METHODS: An apnea-hypopnea index (AHI) ≥ 15 was confirmed in 28/38 patients screened by finger pulse oximetry during overnight ventricular pacing at a backup rate of 40 bpm (BUV40). These patients (23 men, 77.9 ± 7.6 y, BMI 27.6 ± 5.1 kg/m(2)) were randomly assigned to 2 consecutive nocturnal ventilation polygraphies with BUV40 versus OVP at 20 bpm above the mean nocturnal heart rate observed during screening. RESULTS: During BUV40 versus OVP, (1) mean heart rate was 49 ± 8 versus 71 ± 8 bpm (p < 0.0001) and percent ventricular pacing 36% ± 38% versus 96% ± 6% (p < 0.0001); (2) AHI was 35.4 ± 11.9 versus 32.5 ± 15.5 (p = ns), central AHI 23.9 ± 11.8 versus 19.1 ± 12.7 (p < 0.001), and obstructive AHI 11.6 ± 13.1 versus 13.5 ± 15.9 (p = ns). In 15/28 patients without HF, mean left ventricular ejection fraction (LVEF) was 51% ± 17%, AHI was 37.6 ± 11.0 during BUV40 and 39.0 ± 11.5 during OVP, versus 32.8 ± 12.9 and 24.9 ± 16.5 in 13/28 patients with HF (p = 0.02) and mean LVEF 35% ± 15% (p = 0.01). Between the 2 subgroups, (1) central AHI was 23.6 ± 12.4 during BUV40 and 21.5 ± 14.0 during OVP versus 24.1 ± 11.6 and 16.2 ± 10.7 (p = 0.05); (2) obstructive AHI was 14.0 ± 13.7 during BUV40 and 17.6 ± 16.5 during OVP versus 8.8 ± 12.3 and 8.7 ± 14.3 (p = ns). CONCLUSIONS: The prevalence of SA, predominantly central, was high in our pacemaker recipients with permanent AF. In those with HF, a single overnight OVP resulted in modest improvement in central events. CITATION: Bordier P; Maurice-Tison S; Ramana NK. Overdrive ventricular pacing in pacemaker recipients with permanent atrial fibrillation and sleep apnea. J Clin Sleep Med 2012;8(3):257-264.